Evolution of State Ruling - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
The concept of ruling a state was investigated by Machiavelli as early as in the sixteenth century. The concept gradually developed throughout centuries and finally achieved a certain level of maturity in today's politics. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Ruling; government; politics; power; state; sovereignty